The effect of being diagnosed with human papillomavirus infection on women's sexual lives. Issue 8 (18th December 2019) - Alay, Ismail; Kaya, Cihan; Karaca, Ibrahim; Yildiz, Sukru; Baghaki, Sema; Cengiz, Huseyin; Ekin, Murat; Yasar, Levent
Abstract: Problem: Objective studies that use validated questionnaires are needed to evaluate the changes in the sexual functions of women diagnosed with human papillomavirus (HPV) infection. Method of Study: The study comprised 80 sexually active women diagnosed with a high‐risk HPV infection. These patients were divided into four groups as follows: group 1, HPV 16/18‐positive and normal cytology; group 2, HPV 16/18‐positive and abnormal cytology; group 3, non‐16/18 HPV‐positive and abnormal cytology; and group 4, non‐16/18 HPV‐positive and normal cytology. The sexual functions and anxiety statuses of the patients were assessed via the Female Sexual Function Index (FSFI) and Beck anxiety inventory (BAI) questionnaires, respectively, at their first clinical visits and then 2 months later. Results: There was no statistically significant difference among the study groups in terms of the overall FSFI and domain sub‐scores at either of the visits. Women who tested positive for the high‐risk HPV 16/18 strains had a significantly less sexual desire after being informed about the test results. Those with HPV 16/18 and normal cytology had significantly higher anxiety levels at their second than first visits. The BAI scores of the HPV 16/18‐positive women (normal or abnormal cytology) at the second visit were significantly higher than those of non‐16/18 HPV‐positive women with normal cytology. There was no significant difference between the patients with normal and abnormal cytology results regarding the difference of BAI, overall and domain FSFI sub‐scores at the first and second visits. The desire and lubrication domain scores of the HPV 16/18‐positive patients significantly decreased after the first visit compared with those of the non‐16/18 HPV‐positive patients. Conclusion: HPV 16/18 positivity decreases women's total FSFI and desire domain sub‐scores. Highlights: Being diagnosed with HPV 16/18 has more negative effects than other HPV genotypes on women's sexual lives. Healthcare providers should be aware that a positive HPV test result (especially HPV 16/18) may have negative effects on women's sexual lives when sharing the results with their patients. Detecting the affected patients is important to provide them appropriate healthcare support.